2016
DOI: 10.1364/oe.24.00a898
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the angle-independent photon harvesting in organic homo-tandem solar cells

Abstract: Abstract:The effective device photo current of organic tandem solar cells is independent of the angle of light incidence up to 65°. This feature renders these devices particularly suitable for stationary applications where they receive mainly indirect light. In a combined experimental and simulative study, we develop a fundamental understanding of the causal absorption and charge generation mechanisms in organic homo-tandem solar cells. A 3-terminal tandem device architecture is used to measure the optoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, in practical scenarios the solar cell is not constantly oriented in such direction but there is rather a certain angle of incidence. Mertens et al tried to understand a peculiar behavior of organic tandem solar cells, already reported by Riede et al for evaporated tandem cells. In detail, when their device was at a certain angle of orientation Θ with respect to the direction of incidence of light, the short‐circuit current density corrected for the effective area of illumination ( J* SC = J SC /cos( Θ )) was relatively insensitive to this angle, up to 65° .…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in practical scenarios the solar cell is not constantly oriented in such direction but there is rather a certain angle of incidence. Mertens et al tried to understand a peculiar behavior of organic tandem solar cells, already reported by Riede et al for evaporated tandem cells. In detail, when their device was at a certain angle of orientation Θ with respect to the direction of incidence of light, the short‐circuit current density corrected for the effective area of illumination ( J* SC = J SC /cos( Θ )) was relatively insensitive to this angle, up to 65° .…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…Mertens et al tried to understand a peculiar behavior of organic tandem solar cells, already reported by Riede et al for evaporated tandem cells. In detail, when their device was at a certain angle of orientation Θ with respect to the direction of incidence of light, the short‐circuit current density corrected for the effective area of illumination ( J* SC = J SC /cos( Θ )) was relatively insensitive to this angle, up to 65° . In their work, the authors showed that both the measured and modeled EQE spectra of the individual subcells change according to Θ .…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…To efficiently handle the huge parameter space, we performed comprehensive optical device simulations . Based on these simulations Figure a depicts the normalized number of absorbed photons N *( θ )= N /cos( θ ) within the photoactive layer versus the angle θ , depending on the thicknesses of the photoactive layer and the PEDOT:PSS electrode.…”
Section: Resultsmentioning
confidence: 99%
“…To efficiently handle the huge parameter space,w ep erformed comprehensive optical device simulations. [17,18] Based on these simulations Figure 2a depicts the normalized number of absorbed photons N*(q) = N/cos(q)w ithin the photoactive layer versus the angle q,d epending on the thicknesses of the photoactivel ayer andt he PEDOT:PSSe lectrode. N and N*(q)d irectly relate to J sc and J sc *(q)t hrough the internal quantum efficiency,w hich, however, may be dependentont he layer thickness and illumination intensity.F or technical reasonsi nt he subsequent device fabrication, the ITO layer thickness was kept constant.…”
Section: Optical Solar Cell Optimizationmentioning
confidence: 99%
“…This material is surprisingly used only in a few studies in the literature and never used in an OLED device to our knowledge. [49][50][51] The issue of the poor wetting of an electrode material on top of the emissive area also arises when a hole-injection layer (HIL) material is deposited on top of the emissive area. PEDOT:PSS Al4083 is widely used as a HIL layer in direct devices but it is rather difficult to form a homogeneous layer in an inverted device.…”
Section: Introductionmentioning
confidence: 99%